Effect of sulfated polysaccharides on the digestion of DNA by pepsin under simulated gastric juice in vitro. Issue 2 (13th February 2020) - Zhang, Jing; Li, Qian; Jiang, Xiaochen; Li, Xiaojing; Dong, Ping; Li, Jing; Komiyama, Makoto; Liang, Xingguo
Abstract : Sulfated polysaccharide can inhibit the degradation of dietary DNA by pepsin, mainly driven by the interaction between polysaccharides and DNA, secondly polysaccharide and pepsin. Abstract : The effect of sulfated polysaccharides on the digestion of dietary DNA by pepsin was studied using in vitro simulated gastric juice. The results showed that fucoidan (FUC), dextran sulfate (DS) and chondroitin sulfate (CS) could inhibit the digestion of DNA in a dose-dependent manner. Polysaccharides with high sulfate group content have stronger inhibition ability. Fluorescence spectroscopy results showed that polysaccharides could bind to pepsin, and transmission electron microscopy (TEM) confirmed that polysaccharides can interact with DNA, which not only is the main reason that polysaccharides inhibit the digestion of DNA by pepsin but also causes the digestion of DNA by DNase II to be inhibited. The finding suggests that the digestion of DNA should be reevaluated when eating foods rich in sulfated polysaccharides. This study enriched the known pharmacological properties of sulfated polysaccharides as pepsin inhibitors and provided inspiration for the use of sulfated polysaccharides as oligonucleotide drug delivery carriers.